Mobile application for music synthesis using tangible blocks - Ong, You Ping (2019)
This project explores the possibility of creating or recreating musical rhythms in real-time using tangible objects, which would be detected via the rear camera of a mobile device. As such, an application with tangible interaction was developed through this project. Color Blob Detection algorithm provided in the OpenCV library was used for detecting tangible objects and the SoundPool library was used for synthesising of instrument sounds. A user study was conducted to determine the usability of the application developed. Participants of the user study were required to complete tasks requiring replication and creation of rhythmic percussive patterns. Results from the study shows that application with tangible interaction was highly acceptable for users from both musical and non-musical background, with some areas of improvement needed.